Effect of intensive nutrition intervention on nutritional status, hand grip strength, and quality of life on malnourished pre-operative gynecological cancer patients at a cancer institute - Mohammad, Aini Masitah (2021)
Recently, emerging studies conducted to explore the effect of nutrition intervention (NI) pre-operatively, however, none sample GC patients. Those studies also unable to demonstrate benefit of NI to malnourished patient and finding in those studies were not comprehensive. Adopting an open label randomised control trial, this study aimed to identify intensive nutrition intervention (INI) (individualized dietary counselling, oral nutrition supplements [ONS], telephone counselling and home visit follow-up) can improve outcomes among patients with gynecological cancer (GC) during pre-operative period. Results of this study also could help documented the urgent need of screening for risk of malnutrition during 1st visit at clinic and the need to provide continuous professional support to malnourished cancer. Selected GC patients stage 1 to 4, planned for surgery, age >18 years old, were randomly grouped into control group (CG) (n= 35) and intervention group (IG) (n=34). Malnutrition screening tool (MST) was used as a screening tool, while the Patient-Generated Subjective Global Assessment (PG-SGA) was used as a nutrition assessment tool. IG patients received an intensive individualized dietary counselling with the supply of ONS at baseline (Day 1). This continued with telephone counselling and home visit follow-up by research dietitian (Day 3 and Day 6). Meanwhile, CG patients only received general nutritional counselling without supply of ONS. Final assessment was conducted on Day 14. The primary outcomes were weight changes measured using TANITA and dietary intake assessment using 24-hour diet recall. Secondary outcome was Quality of Life assessed using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire version 3.0 (EORTC QLQ-C30) and functional status assessed using Handgrip strength (HGS). The mean duration of INI was 14 days. About 84% of GC patients were categorized as PG-SGA B and 16% were categorized as PG-SGA C, at baseline. At the end of treatment period, there was a significant weight changes between groups (p<0.001) with 0.14% weight gain in IG and 1.3% weight reduction in CG. The mean energy and protein intake of IG patients were higher compared to CG patients by 329 kcal/day and 12.2 g/day, respectively (p<0.001). Appetite and emotional scale (EORTC QLQ-C30 scale) significantly improve after the intervention (p=0.001 and p=0.003, respectively). Meanwhile, no significant changes observed in HGS (p= 0.69). This study shows that INI that incorporated individualized dietary counselling, ONS, telephone counselling and home visit follow-up able to increase energy and protein intake of GC patients, resulting in weight gain. Thus, all GC cancer patients should be screen for risk of malnutrition upon presented to clinic and those found malnourished should be intervene by dietitian earlier by incorporating INI.